Effect of postharvest storage conditions on the colour and freshness parameters of raw honey. (10th August 2013) - Visquert, Mario; Vargas, Maria; Escriche, Isabel
Summary The influence of temperature (25, 30, 35 and 40 °C) and storage time (up to 62 or 104 days) on colour; hydroxymethyl furfural (HMF) content; and diastase index (ID) of citrus, rosemary, eucalyptus, polyfloral and honeydew honey was evaluated. Decreases in luminosity, whiteness index, hue and chroma with the increase in temperature and storage time were observed to different extents depending on the botanical origin of the honey. At all temperatures, the highest values of chromatic parameters throughout the whole period of storage corresponded to citrus honey. Honeydew honey showed the lowest values and the fewest colour differences. Principal component analysis explained 89% of the variations. PC1 (73%) separated honey types at lower temperatures in terms of colour parameters. PC2 (16%) described variations in HMF and ID in relation to storage conditions. Honey type had a much greater influence on HMF, ID and colour than storage conditions. The evaluated postharvest treatments did not alter the characteristic colour of each type of honey as long as the commercial requirements for freshness parameters were met.